Teacher questions and student responses in case-based learning: outcomes of a video study in medical education - Martin Gartmeier; Theresa Pfurtscheller; Alexander Hapfelmeier; Marc Grünewald; Janina Häusler; Tina Seidel; Pascal O. Berberat (BMC Medical Education, 2019)
Abstract Background Case-based learning (CBL) is a highly interactive instructional format widely used in medical education. One goal of CBL is to integrate basic biomedical knowledge and its application to concrete patient cases and their clinical management. In this context, we focus the role of teacher questions as triggers for reproductive vs. elaborative student responses. Specifically, our research questions concern the kinds of questions posed by clinical teachers, the kinds of responses given by students, the prediction of student responses based upon teacher questions, and the differences between the two medical disciplines in focus of our study, internal medicine and surgery. Methods We analyse 19 videotaped seminars (nine internal medicine, ten surgery) taught by clinicians and attended by advanced medical students. Multiple raters performed a low-inference rating process using a theory-based categorical scheme with satisfactory interrater-reliability. Results We found that medical teachers mostly posed initial (instead of follow-up) questions and that their questions were more often closed (instead of open). Also, more reasoning (than reproductive) questions were posed. A high rate of student non-response was observed while elaborative and reproductive student responses had a similar prevalence. In the prediction context, follow-up reasoning questions were associated with low non-response and many elaborative answers. In contrast, the highest student non-response rate followed open reproduction questions and initial reasoning questions. Most reproductive statements by students were made following closed reproduction questions. Conclusions These results deepen our understanding of interactive, questions-driven medical teaching and provide an empirical basis for clinical teachers to use questions in didactically fruitful ways.